Caracterización geológica-geotécnica de la vía el Pangui – el Pincho, cantones el Pangui y Yantzaza, provincia de Zamora Chinchipe - Jiménez Ramírez, Ana Gabriela (2022)
The purpose of this research was to carry out the geological and geotechnical characterization of the El Pangui - El Pincho road, in the cantons of El Pangui and Yantzaza, province of Zamora Chinchipe. The work began with a topographic survey at a scale of 1:1000, which served as the basis for the geological survey where it was found that the study sector is mainly comprised of light brown and reddish clashing clays of the Tena formation and sandstones of the Hollin formation, in addition to superficial deposits dominated by sand, silt and clay soils with the presence of sandstone blocks and granitic blocks. The geotechnical characterization was carried out by applying direct and indirect methods. Within the direct methods: 31 test pits were made, obtaining samples at 0.50, 1.00 and 1.50 m depth. In addition, 4 geotechnical borings were made; two located in the Pachicutza river and the other two located in the El Pincho gorge, both on the right margin and the left margin. The samples obtained were tested at the Estsuelcon laboratory according to ASTM standards such as granulometry, moisture content, Atterberg limits and AASTHO and SUCS classifications. Based on the indirect methods: refraction seismic was performed at Absc. 1+750 and 12+990; thus determining the subsoil layers. To perform the stability analysis, the most representative slopes of the study section were modelled and samples of these were taken to perform the direct shear test. Once the data was obtained, the FS was calculated using the Slide 6.0 software employing the Mohr-Coulomb rupture criterion, determining that the slopes of the road under normal conditions demonstrate FS values greater than 1; that is, their state is stable, while in saturated conditions they present FS values below 1; indicating an imminent failure. Keywords: geotechnical characterization, stability analysis, a factor of safety, Mohr-Coulomb.